2013
DOI: 10.1002/rcm.6591
|View full text |Cite
|
Sign up to set email alerts
|

A differential mobility spectrometry/mass spectrometry platform for the rapid detection and quantitation of DNA adduct dG‐ABP

Abstract: RATIONALE: There is continued interest in exploring new analytical technologies for the detection and quantitation of DNA adducts, biomarkers which provide direct evidence of exposure and genetic damage in cells. With the goal of reducing clean-up steps and improving sample throughput, a Differential Mobility Spectrometry/Mass Spectrometry (DMS/MS) platform has been introduced for adduct analysis. METHODS: A DMS/MS platform has been utilized for the analysis of dG-ABP, the deoxyguanosine adduct of the bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…Prior works from our laboratory have demonstrated that the judicious use of modifiers provided conditions for rapid quantitation of selected analytes in matrices of varying complexities [36, 37]. We have shown that, in addition to the rapid analysis time afforded by use of the DMS, sample preparation steps can be minimized or even eliminated by taking advantage of the unique post-electrospray selective ion filtration capabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior works from our laboratory have demonstrated that the judicious use of modifiers provided conditions for rapid quantitation of selected analytes in matrices of varying complexities [36, 37]. We have shown that, in addition to the rapid analysis time afforded by use of the DMS, sample preparation steps can be minimized or even eliminated by taking advantage of the unique post-electrospray selective ion filtration capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has long been involved in the development of DMS technology for analytical applications [14, 30, 36] and in recent years, we have been particularly interested in the use of DMS-MS for quantitative analysis with reduced sample cleanup and minimal or zero LC time [37]. There are a number of advantages to the use of DMS in rapid quantitative biomarker analysis, many previously discussed, as in Coy et al [2], but one point is of special interest when DMS-MS quantitative analysis is compared to LC-MS: LC-MS as well as drift-time or travelling-wave IMS require integration of an ion current over an elution or drift time profile, but DMS-MS intensities for quantitation by infusion are obtained continuously by monitoring the CoV for peak ion transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease both the sample quantities and the limits of detection and quantitation (LOD/LOQ), nanoflow liquid chromatography (LC) has been successfully adopted in many labs including our own [10]. In an attempt to further improve on these latter advances and further reduce the amount of DNA required for the analysis, both we [11-14] and others [15-21] have now adopted a state-of-the-art microfluidic chip-based technology. While the approach also relies on the use of nanoflow LC, in addition, it incorporates on-line sample cleanup procedures that bypass much of the typical manual sample processing to reduce sample losses.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its very high concentration in human and NHP urine, creatinine could be quantified by direct dilution, since high dilution reduces matrix effects effectively [90][91][92][93]. The creatinine calibration curve was generated using a 2500-fold dilution in solvent (50% ACN + 0.1% formic acid) with IS addition.…”
Section: Dms-ms Is a Two-dimensional Separation Technique That Dependmentioning
confidence: 99%
“…The Vouros group is the first to use this platform for analysis of DNA adducts. In 2013, Kafle et al [92] developed a DMS-MS/MS platform for the analysis of dG-C8-4-ABP and achieved a detection limit of one adduct per 10 6 nucleotides using only 2 µg DNA. The detection limit can be greatly improved by using a more sensitive MS instrument as opposed to a prototype DMS system coupled to a 12-year old SCIEX 3000 triple quadrupole.…”
Section: Dms-msmentioning
confidence: 99%